Indonesian Students’ Attitudes towards EFL Learning in Response to Industry 5.0 - Rolisda Yosintha (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
The main objective of this study was to identify the attitudes of Indonesian students towards studying English vis-a-vis their readiness to compete in the fifth industrial revolution era. The data obtained from a four-point scale questionnaire administered to 216 participants from 12 universities across Indonesia were analyzed through a descriptive case study procedure. The findings showed that even though most students had positive attitudes towards EFL learning ( = 3.29) as well as towards Industry 5.0 ( = 3), they did not have the confidence to affirm that they have the instrumental competencies required by the tight competition of Industry 5.0, especially English competencies ( = 2.37). These findings indicate that despite their positive attitudes towards EFL learning, Indonesian students would be possibly not yet ready for Industry 5.0 in terms of their English proficiency. Therefore, it is suggested that policymakers and all education stakeholders take the necessary measures to improve the students’ English skills to ensure that they will be graduates who match the demands of Industry 5.0.